2021
DOI: 10.1080/19401493.2020.1868577
|View full text |Cite
|
Sign up to set email alerts
|

Parametric PGD model used with orthogonal polynomials to assess efficiently the building's envelope thermal performance

Abstract: Estimating the temperature field of a building envelope could be a time-consuming task. The use of a reduced-order method is then proposed: the Proper Generalized Decomposition method. The solution of the transient heat equation is then re-written as a function of its parameters: the boundary conditions, the initial condition, etc. To avoid a tremendous number of parameters, the initial condition is parameterized. This is usually done by using the Proper Orthogonal Decomposition method to provide an optimal ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…With the computational gain, other studies of parametric problems using reduced-order methods are found in the literature. In this way, in [12] they have combined the POD and PGD approach to modeling the soil for application in the study of canyon streets and in [13] to assess efficiently the building's envelope thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…With the computational gain, other studies of parametric problems using reduced-order methods are found in the literature. In this way, in [12] they have combined the POD and PGD approach to modeling the soil for application in the study of canyon streets and in [13] to assess efficiently the building's envelope thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Image signals are subject to several processes such as transmission [1], enhancement [2], transformation [3], hiding [4], and compression [5,6]. Similarly to image processing, speech signals processing is also essential [7], and involves several stages such as transfer [8], acquisition [9], and coding [10]. Pattern recognition, which is considered an automated process, is widely used in various applications such as computer vision [11], statistical data analysis [12], information retrieval [13], shot boundary detection [14], and bio-informatics [15].…”
Section: Introductionmentioning
confidence: 99%